How Service Offerings and Operational Maturity Influence the Viability of Health Information Exchanges. Issue 11 (3rd August 2017) - Khuntia, Jiban; Mithas, Sunil; Agarwal, Ritu
Abstract : Health information exchanges (HIEs) are new organizational forms in the United States that facilitate digital exchange of health data across participants. Many believe that these multi‐sided digital platforms will become key enablers of the digital transformation of healthcare in the United States. However, like other entrepreneurial ventures, HIEs face challenges to achieve operational maturity and financial viability. Entrepreneurial ventures often fail to attain financial viability due to the initial design of the business model and the inability to evolve the model over time. We focus on the influence of service offerings, revenue models, and their evolution on the viability of HIEs. Using a unique archival dataset constructed from surveys of HIEs in the United States from 2008 to 2010, we find that providing an extensive service bundle may lead to higher operational maturity with the HIE's increasing age, but this may deter the HIE's potential to achieve financial viability. The findings also show that the influence of service offerings on financial viability is mediated by operational maturity. Qualitative evidence corroborates these findings and suggests that HIEs need to move from providing a set of foundational services to offering more advanced services as they evolve and that they need to appropriately bundle the services using transaction‐, subscription‐ or mixed‐fee models. We discuss how these findings contribute to research at the intersection of operations management and information systems and offer important implications for HIEs with regard to crafting and evolving appropriate service offerings and revenue models.